Effect of injection pressure on the performance and emission characteristics of niger-dieselethanol blends in CI engine / Bikkavolu Joga Rao ... [et al.] - Joga Rao, Bikkavolu; Srinivas, Vadapalli; Chebattina, Kodanda Ramarao; Gandhi, Pullagura (Universiti Teknologi MARA, 2021)
Biodiesel is promising as the best substitute/alternative fuel to most diesel engines due to its low sulfur content, lower aromatic hydrocarbon, renewable, and more oxygenated fuel. The dried Niger seeds were collected for their oil extraction and biodiesel production in the current research. This paper concerns about the influence of injection pressure on a single-cylinder VCR direct injection diesel engine using Niger oil biodiesel, diesel and ethanol blends, B5+D90+E5 (5% Biodiesel + 90% Diesel + 5% Ethanol), B10+D80+E10 (10% Biodiesel + 80% Diesel + 10% Ethanol) and B15+D70+E15 (15% Biodiesel + 70% Diesel + 15% Ethanol). The performance, combustion, and emission characteristics are observed for the above blends at the various pressures of 180 bar to 220 bar with 20 bar variations. At low injection pressures, the two blends (B5+D90+E5 and B10+D80+E10) show considerable improvement in brake thermal efficiency and mechanical efficiency compared to baseline diesel. At high injection, pressures blend B15+D70+E15 produce higher brake thermal efficiency and mechanical efficiency. Consequently, less brake-specific fuel consumption and less ignition delay period for the blends respectively. The exhaust pipe emissions such as Carbon Dioxide (CO2), Carbon Monoxide (CO), Hydrocarbons (HC), Nitrogen oxides (NOX) are measured at rated power at all injection pressures. CO2, CO, and HC are low at high injection pressure, but NOX increases as injection pressure increases.